PENGARUH STRATEGI BISNIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA KEUANGAN BANK UMUM KELOMPOK USAHA (BUKU) PADA BANK UMUM KONVENSIONAL DI INDONESIA - M. Adriansyah; Fajri Adrianto (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine and analyze the influence of business strategy and corporate characteristics on the financial performance of Commercial Bank Business Group (BUKU) in Conventional Commercial Banks in Indonesia. This research is exploratory research with quantitative method. The sampling technique was conducted by census method with all Bank BUKU 3 and Book 4 which amounted to 18 Banks. This study uses regression analysis of panel data with the help of SPSS program version 22.00. The results showed that efficiency in production and distribution have a negative and significant effect on financial performance, marketing cost and sales efficiency have negative and insignificant effect to company's financial performance. Intensity of asset has negative and insignificant effect to financial performance, firm size has positive and insignificant effect to the financial performance of the company, and the growth rate of DPK has a positive and insignificant effect on the financial performance of the company Commercial Bank Business Group (BUKU) in Conventional Commercial Banks in Indonesia. Keywords: Business Strategy, Company Characteristics, Financial Performance and Commercial Bank of Business Group (BUKU)